2015
DOI: 10.1021/acs.bioconjchem.5b00611
|View full text |Cite
|
Sign up to set email alerts
|

Oxime Catalysis by Freezing

Abstract: Chemical reaction rates are generally decreased at lower temperatures. Here, we report that an oxime ligation reaction in water at neutral pH is accelerated by freezing. The freezing method and its rate effect on oxime ligation are systematically studied on a peptide model system, and applied to a larger chemokine protein, containing a single acetyl butyrate group, which is conjugated to an aminooxy-labeled ligand. Our improved ligation protocol now makes it possible to efficiently introduce oxime-bond coupled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 17 publications
1
36
0
Order By: Relevance
“…Hydrazone catalysis by way of two freeze thaw cycles was utilized to increase drug loading while reducing reaction time. 18 …”
Section: Resultsmentioning
confidence: 99%
“…Hydrazone catalysis by way of two freeze thaw cycles was utilized to increase drug loading while reducing reaction time. 18 …”
Section: Resultsmentioning
confidence: 99%
“…These NMR spectra show overall resonance broadening,w hich we attribute to transient formation of the OPRAH heterodimer.T his is supported by our observations with the He resonances of Tr p57, which is an indirect structural probe owing to its distance from the modified Nterminus of 16.Overall, we conclude that the general folds of the two protein domains,PF4 and RANTES,are maintained in OPRAH, and resonance broadening of the residues at the (16), OPRAH (17)and a1:1 complex of wtRANTES and Met-PF4, under similar conditions. Topspectrum: Overlay of experimental 1 HNMR spectrum of OPRAH (black) and the sum of the spectra of free RANTES (16)and PF4 (8)(broken line) The agreement between experimental spectrum 17 and the summed spectra 8 + 16 shows that, globally,O PRAH consists of two natively folded PF4 and RANTES protein domains. Local differencesa re, however,apparent and these regions correspond to sharp amide peaks in the N-terminus region (amino acids 2-7) of free PF4 that seem to broaden out significantly in OPRAH.…”
Section: Angewandte Chemiementioning
confidence: 93%
“…This observation indicated that the rate of formation of the oxime bond between RANTES and PF4 was accelerated by heterophilic chemokine interactions, which bring the two reactive species into close proximity (Figure 3). In retrospect, the proposed conformation-assisted ligation was supported by the lower-than-expected catalytic effect of aniline.E ventually,u sing slow freezing catalysis, [16] we were able to achieve complete oxime reaction within 2h.…”
Section: Angewandte Chemiementioning
confidence: 98%
“…[48] He furthermorer eporteda no xime ligationr eaction that can be accelerated under aqueous conditions, at low concentrationsa nd at neutral pH by freezing. [49] Phil Dawson (The Scripps Research Institute,U SA) described how as mall combinatorial peptidelibrary can be built through sequential click reactions starting from as ingle parent peptide. Ab icyclic peptide sunflower trypsin inhibitorc ontaining an azide and alkyne moiety was synthesized and sequentially click-reacted with small molecules on reversed-phase (RP) silica.…”
Section: Protein Synthesis Beyond the Ribosome: Advances In Chemical mentioning
confidence: 99%